PENINGKATAN DISIPLIN KERJA GURU MELALUI PEMBINAAN KOMPETENSI KEPRIBADIAN - Madin Madin Madin (UNIVERSITAS BENGKULU, 2016)
The objective of this study is to describe the increasing discipline of teachers by creation personal competence of public elementary school 25 Ketahun, North Bengkulu. Thisstudy used descriptive qualitative, the subject of this study was principal and teachers of public elementary school 25 Ketahun, North Bengkulu. The data were collected by interview,observation, and documentation. The data of this study was analyzed by using inductive include of three activity namely reduction of data, serve of data, and drawing of conclusion. The result of this study showed that teachers of public elementary school 25 Ketahun have processing of discipline, but still need increasing that their doing by using increasing of personal competence.Keywords: personal competence, discipline, teachers